Efektifitas Permainan Kooperatif Merancang Gambar Untuk Meningkatkan Keterampilan Sosial Siswa TK A BAS Tuban - Anindya Purnama (Jurnal Psikologi Tabularasa, 2015)
This study aims to determine the effectiveness of cooperative games through media designed the image to improve the social skills of kindergarten A Bina Anak Sholeh (BAS) Tuban. The method used in this study is a quasi experimental design with nonradomized pretest-posttest control group design. Samples in this study are 32 kindergarten A BAS Tuban selected by using purposive sampling technique. Methods of data collection in social skills using observation checklists and rating scales and measured with reference to the Guttman scale. Prior to the data analysis to test the validity and relaibilitas first. Validity is based on expert judgments (expert judgment), whereas reliabilias test using Cronbach's Alpha SPSS 22:00. The results showed that the effective cooperative ploy used to improve the social skills of kindergarten A BAS Tuban. This is indicated by an increase in social skills score of 76% with the strong category.